Caracterización de las inmunoglobulinas del ñandú (Rhea americana) - Montagna, D.R. (2013)
The aim of this work was to characterize the serum immunoglobulins and egg-yolk IgY from ñandú (Rhea americana), by cellulose acetate electrophoresis, polyacrylamide gel electrophoresis and Westernblot. Nineteen clinically-healthy birds, 14 to 15 month-old were studied, belonging to a farm placed in Balcarce, Buenos Aires province, Argentina. Cellulose acetate electrophoresis showed that four protein fractions were present in serum: albumin, alpha, beta and gammaglobulins. Gammaglobulin concentration was 0.69 ± 0.18 g/dl, with a range of 0.42-1.05 g/dl. Electrophoresis of IgY showed that this immunoglobulin runs together with gammaglobulins. Polyacrylamide gel electrophoresis showed two protein bands with an approximate molecular weight of 65 and 25 kD, compatible with IgY heavy and light chain, that could be seen in serum as well as in purified IgY. A goat anti-ñandú IgY was produced and utilized in a Western-blot, in which it recognized a 65 kD-protein band, both in serum and in purified IgY. This anti-IgY could allow the development of diagnostic tools to study the presence of the causative agents of infectious diseases in Rhea populations.